Protective effect of lycopene on oral mucositis and antioxidant capacity of blood plasma in the rat exposed to gamma radiation - Mina Motallebnejad; Shaghayegh Zahedpasha; Ali Akbar Moghadamnia; Sohrab Kazemi; Daryoush Moslemi; Mahdi Pouramir; Fariba Asgharpour (Babol University of Medical Sciences, 2020)
Background: Nowadays, radiotherapy is used effectively for treatment of head and neck cancers. Mucositis is one of the most important side effects of radiotherapy. Radio-protective agents protect tissues and cells against the adverse effects due to ionizing radiation and cleave radiation-induced free radicals. Lycopene as a potent antioxidant protects cells against oxidative damage by free radical-scavenging.  The present study investigated the antioxidant effect of lycopene on oral mucosa of irradiated rats. Methods: In this experimental animal study, 28 rats were placed in four groups as follows: treated with 50 mg /kg of lycopene (L50), solvent+irradiation (SR), 25 mg / kg of lycopene+irradiation (LR25), and 50 mg / kg of lycopene+irradiation (LR50). The rats received lycopene intraperitoneally. On the irradiation day (day 0) and tenth day of radiation, blood samples were taken from the animals for FRAP and TBARS tests. Results: The results showed that the LR50 group didn't show mucositis higher than Grade 2. There was a significant difference (p <0.05) between SR and the L50 regarding the severity of mucositis. In addition, L50 showed higher antioxidant activity and lower peroxidation than SR. Conclusion: The lycopene reduced the severity of mucositis. Therefore, it can be used as a potential and promising nutritional substance to prevent radiotherapy complications, especially in the treatment of head and neck cancers. However, further research is necessary to confirm these results.